Sistem Pendukung Keputusan Pemilihan Sampah Tempat Sementara di Kota Kupang menggunakan Metode Topsis (Journal Innovations Computer Science, 2023)
Temporary waste management in the city of Kupang is an urgent problem to ensure a clean and healthy environment. Selecting the right location for a temporary waste bin is an important step in efficient waste management. In this context, Decision Support Systems (DSS) can provide valuable assistance in the decision-making process. This research proposes a Decision Support System for Selection of Temporary Waste Bins using the TOPSIS Method. The TOPSIS method (Technique for Order of Preference by Similarity to Ideal Solution) is an effective method for overcoming multi-criteria decision-making problems. This system will integrate various factors such as distance to settlements, population density, accessibility, and other environmental factors to evaluate and select optimal temporary waste bins. This decision support system will provide stakeholders, including city governments, waste management authorities, and the community, with tools that can be used to make more informed decisions in determining the location of temporary waste bins. The results of the Decision Support System analysis will provide recommendations based on the level of preference for the specified criteria, enabling stakeholders to make more informed and sustainable decisions in city waste management. It is hoped that this research can help improve efficiency in temporary waste management in Kupang City and has the potential to become a model for other cities that face similar challenges in waste management.